EVALUATION OF SOYBEAN FLOURS OBTAINED FROM WHOLE AND SHELLED GRAINS SUBJECTED TO HEAT TREATMENT - Aline Andressa Rigo; Alice Maria Dahmer; Steffebs, Clarice; Steffens, Juliana; Leite, Rodrigo Santos; José Marcos Gontijo Mandarino; Mercedes Concórdia Carrão-Panizzi (Revista Tecnológica, 2023)
This study aimed to obtain and characterize soy flours from whole (WG) and shelled grains (SG) of the conventional cultivar Vmax and special cultivars used for human consumption, BRS 267 and BRS 257. For lipoxygenase enzyme inactivation, the WGs and SGs of BRS 267 and Vmax were bleached at 98 °C for 5 min, roasted at 150 °C for 30 min, milled and finally sieved through a size 40 mesh to obtain the flours. These flours were analyzed for proteins, lipids, isoflavones, Kunitz trypsin inhibitor, their nitrogen solubility index and their protein dispersibility index. The grain heat treatments caused a reduction in protein solubility, an increase in aglycone isoflavones and an 80% reduction in levels of the Kunitz trypsin inhibitor. Flours from bleached WGs were brown in color. Flours from BRS 267 had higher protein levels, while those from the cultivar Vmax had the highest lipid content. Flours from BRS 257 had greater protein solubility. Thus, varieties of special soybeans, genetically enhanced for human consumption, can be processed for better quality soy foods, promoting their acceptance.